An Autonomous Field Robot Farmbeast : The Field Robot Event 2023 Edition - Popič, Gregor; Naveršnik, Urban; Rakun Kokalj, Jaša Jernej; Rihter, Erik; Rakun, Jurij (Agricultura Scientia, 2025)
In contemporary agricultural automation, the demand for highly adaptive autonomous systems is rapidly increasing. Addressing this need, we introduce the latest iteration of FarmBeast, an advanced autonomous robot designed for precise navigation and operation within the complex terrain of cornfields. This paper details the technical specifications and functionalities of FarmBeast, developed by a Slovenian student team from the University of Maribor for the international Field Robot Event (FRE) 2023. The enhanced version features significant hardware and software upgrades, including a completely new robotic platform, a multichannel LIDAR system, an Xsens IMU, and advanced algorithms for efficient row navigation and weed removal. These integrated technologies aim to improve the efficiency and reliability of agricultural processes, reflecting the broader trend towards digitization and precision farming. Participation in international competitions like FRE provides a valuable platform for students to apply interdisciplinary knowledge, fostering the development of practical skills and understanding the interconnectedness of various scientific disciplines. As highlighted in the results section, FarmBeast performed notably compared to other 14 robots, securing top-five finishes in navigation, plant treatment, and obstacle detection tasks, demonstrating its capabilities in dynamic agricultural settings.
Keywords: precision agriculture; robotics; sensors; algorithms